World curriculum and accountancy teaching: a comparative study of accounting science - Kouloukoui, Daniel; Ribeiro da Silva, Antonio Carlos; Bezerra Gabriel, José Ronaldo; Gonzaga Andrade, Jacilene Oliveira (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The purpose of this work was to analyze the curriculum matrices of Accounting Science undergraduate programs of higher education institutions in France and Brazil as well as to compare them to the World Curriculum (WC), proposed by ISAR, a work group of United Nations Conference on Trade and Development (UNCTAD). To achieve this, an exploratory research was performed based upon a document analysis of institutional information from 10 French and 10 Brazilian universities. After gathering and sorting the data, a descriptive study was carried out to check for similarities between the undergraduate program curricula and the WC. Among other findings, it was disclosed 72% of the French universities and 61% of the Brazilian ones had curriculum matrices correlated to the WC. It was concluded that, from an all-encompassing viewpoint, the university curriculum matrices of both countries are close to the WC.